Conceptual Reverse Logistics Model used by Online Retailers Post Covid-19 Lockdown - Purvi Kushwaha (Universitas Prasetiya Mulya, 2021)
Coronavirus disease (Covid-19) is an infectious disease caused by a newly found coronavirus. Coronavirus 2(SARS-CoV-2), caused an illness known as Covid-19, which was similar to SARS and was characterized usually by fever and breathing symptoms. World Health Organization in March 2020 declared Covid-19 as pandemic. Social distancing is the only measure in the absence of any vaccine to reduce the spread of this virus so many countries including India are going under lockdown. In the lockdown, the Government ordered closure of all the brick-and-mortar businesses. In this time of crises customers have only choice to purchase essential products from e-commerce portals. Prime Minister Narendra Modi announced that essential items could be purchased through e-commerce portals, all e-commerce businesses were instructed by the Ministry of Consumer Affair to take proper precautions and hygiene in their entire supply chain process. This paper suggests a model to incorporate hygiene in reverse logistics for online retailers post lockdown. https://doi.org/10.21632/irjbs.14.3.229-234